Physiological Response Of Groundnut (Arachis hypogaea L.) Genotypes Under Moisture Stress Condition (Journal of Pharmaceutical Negative Results, 2022)
Groundnut (Arachis hypogaea L.) is an important oil seed crop and can be affected by moisture stress during critical stages. Moisture stress is most important factor which can limit crop growth and yield by altering various physiological processes. In the current study physiological response of groundnut genotypes were studied on both moisture stress and moisture stress free condition. Pot experiment was conducted with three replication in Complete randomized block design with factorial arrangement at Sananandal village in theThiruvannamalai district, of Tamilnadu (March to June 2020) to evaluate the physiological response of 10 released groundnut varieties (VRI 2, VRI 6, VRI 8, TMV 7, TMV 13, TMV 14, K 6, JL 24, DHARANI, CO 3) and three cultures (VG 19721, VG 18089, VG 17008) under moisture stress free and moisture stress condition. Physiological response was assessed in terms of Relative water content (RWC %), Membrane stability index (MSI) and Drought tolerance efficiency (DTE %). The moisture stress was imposed by withholding the irrigation from flowering to pod initiation stage for stressed pot and regular irrigation was given for non-stressed pots.Observations were recorded for Relative water content (RWC %), Membrane stability index (MSI) and Drought tolerance efficiency (DTE %) for pod yield. Among the genotypes TMV 7 and VRI 6 is found to be superior and CO 3 recorded the lowest values on RWC (%), MSI, and DTE (%) respectively.